School Well-Being Relationships with Achievement Motivation in Primary School: A Study of Positive Psychology in Pandemic (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
This study aims to determine the existence of a positive and significant relationship between school well-being and achievement motivation of fifth grade primary school students. This type of research is correlational quantitative with Likert scale data collection techniques, thats the school well-being scale of 19 items and the achievement motivation scale of 22 items. The population in this study were 2427 students of fifth grade public elementary school. The research sample used simple random sampling with a total of 336 students. The data analysis technique uses Rank Spearman correlation with the calculation of r equal to 0.418 which indicates that the relationship between school well being variable and achievement motivation is in the sufficient category. Then the results also obtained thit > ttabel that 8.58 > 1.967. Based on the results of the study, it shows that there is a positive and significant relationship between school well-being and the achievement motivation of fifth grade primary school students. This research can be more optimal if researchers can direct observations to schools after the pandemic period ends and this research can be followed up by further research by observing aspects outside of school well-being and achievement motivation.